Low-concentration and multi-component NMHCs capture from oil field exhaust using porous ZIF-8/iso-hexadecane slurry - Kun Li; Han Tang; Jin Cai; Chun Deng; Bei Liu; Yunlei Peng; Changyu Sun; Guangjin Chen (Green Chemical Engineering, 2024)
Non-methane hydrocarbons (NMHCs) are a common type of volatile organic compounds (VOCs) pollutant in the petrochemical industry and have attracted widespread attention because of their adverse health effects and environmental impacts. In this paper, we report a new porous slurry formed with zeolitic imidazolate framework-8 (ZIF-8) and iso-hexadecane to capture the low-concentration and multi-component NMHCs (mainly ethane (C2H6), propane (C3H8), and n-butane (n-C4H10)) from the oil field exhaust. The sorption capacity of C2H6 in the slurry is significantly higher than that of nitrogen (N2) and methane (CH4). Moreover, the slurry demonstrated a clear advantage for C2H6 over N2 and CH4 in competitive adsorption through the pressure-drop curves. In the NMHCs capture experiments, the C3H8 and n-C4H10 concentrations after purification can be reduced to below 100 ppm, while the C2H6 concentration can reach approximately 180 ppm. More encouragingly, in the breakthrough tests, the slurry exhibits a perfect kinetic separation selectivity for multi-component NMHCs. Furthermore, to avoid structural collapse of ZIF-8 material during long-term use in acidic and wet environments, a certain amount of 2-methylimidazole was retained in the slurry as a protective agent in the material synthesis process. In this way, the ZIF-8 materials in the slurry can retain the stable characteristic structure in an aqueous and acidic environment and keep the capture capacity for NMHCs without degradation. We believe the porous ZIF-8/iso-hexadecane slurry is a promising capture agent for low-concentration and multi-component NMHCs with strong purification capacity and stability.